Ginsenoside Rg1 promotes bone marrow stromal cells proliferation via the activation of the estrogen receptor-mediated signaling pathway - Lu Xin-zheng; Wang Jim-hong; Wu Xin; Zhou Lei; Wang Li; Zhang Xiao-wen; Cao Ke-jiang; Huang Jun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the possible mechanisms of ginsenoside Rg1 promoting bone marrow stromal cell (BMSC) proliferation. Methods: BMSC were isolated from bone marrow of Sprague-Dawley rats and maintained in vitro. After stimulation with 1 μmol/L ginsenoside Rg1 for the indicated time, the proliferation ability of BMSC were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and [3 H]-thymidine incorporation assays. The estrogen receptor (ER) binding activity of BMSC was determined by a specific ER antagonist and an ER binding assay. Furthermore, the influence of ginsenoside Rg1 on the expression of ERα was investigated by RT-PCR and Western blotting assays. Results: BMSC proliferation stimulated by 1 μmol/L ginsenoside Rg1 can be completely blocked by 1 μmol/L ER antagonist ICI 182, 780, or ERα-specific antagonist methylpiperidinopyrazole. Moreover, Rg1 failed to displace the specific binding of [3 H]17 β-estradiol to BMSC cell lysates, suggesting that no direct interaction of Rg1 with the ER is needed for its estrogenic effects. In addition, 1 μmol/L Rg1 had no effects on the expression of ERα in either the mRNA or protein levels. Conclusion: Our results indicate that ERα is essential for mediating the effects of Rg1 on stimulating BMSC proliferation, which might involve the ligand/receptor-independent activation of ERα.